Perencanaan Rancang Bangun Microstrip Band Pass Filter dengan Struktur Tapped Input Hairpin pada Aplikasi Jaringan Mid-band 5G Telkomsel - Prijono, Wahju Adi; Rizki, Naufal Kurnia (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2022)
Microstrip filter is a type of Radio Frequency (RF) filter that uses a thin electrical conductor separated from the ground plane by using a dielectric called the substrate. Microstrip filters are generally printed on Printed Circuit Boards or PCBs where high-frequency signals are directed from one part of the system to another with high efficiency. There are several types that can be applied to the operation of microstrip filters, one of which is a band pass filter. Band pass filter is a filter that can pass a signal with a certain frequency that is limited by a low cut-off frequency and a high cut-off frequency, and is able to dampen signals that are below the cut-off frequency and above the high cut-off frequency. There are several types of resonator designs that can be used for reference in the manufacture of microstrip filters, such as tapped line input hairpin filters, stub loaded filters, stepped impedance filters, and combline filters. By using the reference form of the tapped line input hairpin, this journal is intended for planning the manufacture of microstrip filters in the application of Telkomsel's 5G technology.